Survey of Blowfish Algorithm for Cloud - Ezadeen, Shamil; Alwattar, Auday H (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Abstract. Security is the study of encryption and decryption, data hiding, potential attacks, and performance evaluation. Many algorithms perform this purpose. Blowfish is a symmetric block cipher that uses the Feistel network. Although several works employed the Blowfish algorithm for the security of the cloud, there is still no article that lists previous studies. Cloud computing is the transmission of computer services such as servers, storage, databases, networking, software, analytics, and intelligence through the Internet ("the cloud") in order to provide faster innovation, more flexible resources, and cost savings. The most common issue with cloud computing is information security, privacy, confidentiality, and how the cloud provider ensures these services. This paper includes a survey of most previous works that were concerned with using the Blowfish algorithm in achieving cloud security